Saber do espaço e colonização regional: constituição territorial e expedições geográficas no sudoeste do Paraná - Aruanã Antônio dos Passos; Nair Sanzovo Pivatto (Confins)
The text analyzes a set of expeditions and research trips s and studies carried out simultaneously with the process of colonization and development of the Southwest region of the State of Paraná, between the decades of 1940 to 1970. It tries to map the diverse expeditions and its work of Diagnosis and recording of the physical and human characteristics of colonization and intensified territorial reoccupation after the 1940s with the governmental incentive for the movement of population cams from the extreme south of the country (Santa Catarina and Rio Grande do Sul) to the Southwest region of Paraná. The history of these geographical expeditions reveals a new look at the process of occupation and exploitation of the natural resources of the region, while they served to construct a set of spatial knowledge disseminated through the main scientific geographic magazine of that context: the Brazilian Journal of Geography , Linked to the Brazilian Institute of Geography and Statistics, a governmental body of extreme importance in the formulation of strategic planning and diagnostics focused on territorial sovereignty and proposing solutions to national problems.